A tale of two explanatory styles in cognitive psychology. (October 2019) - Shapiro, Lawrence
The development of a theory of mechanistic explanation has been a welcome advance over previous theories of explanation, such as deductive nomological explanation. However, despite the claims of some supporters of mechanistic explanation, not all explanation in cognitive science is or should be mechanistic. I defend the claim that functional analysis remains a distinct and legitimate form of explanation within cognitive science.